2016
DOI: 10.1541/ieejjia.5.61
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Linear Feedback Position Control in Presence of Presliding Friction

Abstract: In various servo applications, the design of a precise positioning control constitutes a trade-off between the fast transient response and the short settling time for the required accuracy. Mostly, neither 'universal' control gains can be found to be equally suitable for both of these objectives. In this study, the design of a cascaded precise positioning control is analyzed in the presence of nonlinear friction. The nonlinear friction strongly impacts the reference settling and can deteriorate the positioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The design of a more general nonlinear friction observer was provided in Ruderman and Iwasaki (2015), especially for motion control applications. The performance limitations of the cascaded P-PI motion controls with respect to nonlinear friction rejection at micro-positioning were discussed in Ruderman and Iwasaki (2016); Ruderman (2016). The authors demonstrated that zero steady-state positioning error is nearly impossible with linear controllers.…”
Section: Introductionmentioning
confidence: 99%
“…The design of a more general nonlinear friction observer was provided in Ruderman and Iwasaki (2015), especially for motion control applications. The performance limitations of the cascaded P-PI motion controls with respect to nonlinear friction rejection at micro-positioning were discussed in Ruderman and Iwasaki (2016); Ruderman (2016). The authors demonstrated that zero steady-state positioning error is nearly impossible with linear controllers.…”
Section: Introductionmentioning
confidence: 99%
“…In 1902, Stribeck showed a continuous, velocity-dependent decrease from static to Coulomb friction levels [76], commonly present in lubricated contacts and widely known as the Stribeck effect. Further developments have led to dynamic friction models to accommodate for presliding effects (see, e.g., [5,74]), such as the Dahl model [32], the LuGre model [26], or the ones in [77,4].…”
Section: Introductionmentioning
confidence: 99%
“…Gearbox lubricants introduce viscous friction, while heat losses in the drive (eg, due to eddy currents), may change viscosity under operation. Static friction (stiction) significantly contributes to the degrading of the linear axes positioning, especially during motion onsets and axes reversals . Sufficient knowledge of the occurring frictional phenomena not only facilitates better control loops but may also infer information about the levels of equipment wear.…”
Section: Introductionmentioning
confidence: 99%